Expert consensus regarding drivers of antimicrobial stewardship in companion animal veterinary practice: a Delphi study. (16th June 2018) - Currie, Kay; King, Caroline; Nuttall, Tim; Smith, Matt; Flowers, Paul
Abstract : Antimicrobial resistance (AMR) is a global challenge facing both human and animal healthcare professionals; an effective response to this threat requires a 'One‐Health' approach to antimicrobial stewardship (AMS) to preserve important antibiotics for urgent clinical need. However, understanding of barriers and enablers to effective AMS behaviour in companion animal veterinary practice is currently limited. We conducted a Delphi study of 16 nationally recognised experts from UK‐based veterinary policymakers, university academics and leaders of professional bodies. This Delphi study sought to identify veterinary behaviours which experts believe contribute to AMR and form vital aspects of AMS. Analysis of Delphi findings indicated a perceived hierarchy of behaviours, the most influential being antibiotic prescribing behaviours and interactions with clients. Other veterinary behaviours perceived as being important related to interactions with veterinary colleagues; infection control practices; and the use of diagnostic tests to confirm infection. Key barriers and enablers to AMS within each of these behavioural domains were identified. Specific interventions to address important barriers and enablers are recommended. To the authors' knowledge, this is the first study to establish expert consensus at a national level about which 'behaviours' (aspects of veterinarian practice) should be targeted in relation to AMR and AMS in companion animal veterinary practice.